DOES GROUP RE-GROUP STRATEGIES IMPACT ON STUDENT’S TEXTS INTERPRETATION? - Onovughe, Ofodu Graceful (European Scientific Journal, ESJ, 2012)
The main pursuit of the present paper is to examinethe impact of group re-group strategies on students’ texts interpretation. The focus of this study is on the use of two metacognitive strategies in empowering learners to become effective readers. Using a pretest and posttest control group design through the reading comprehension test, the researcher tested the effect of the group re-group strategies on learners’ ability to interpret texts.